Interest, Emotional Intelligence, and Intellectual Intelligence on PJOK Learning Achievement in Middle School Students - Usman, Arifuddin; Anggreni, Juharti; Hudain, Muh. Adnan; Bustang; Hanafi, Suriah (Education and Talent Development Center Indonesia (ETDC Indonesia), 2024)
This research objective is to determine the relationship between interest in learning, emotional intelligence, and intellectual intelligence and the PJOK learning achievement of class IX students at Public Middle School 1 Keera. The sample consisted of 54 students selected through random sampling. The research's dependent variable is the PJOK learning achievement. The independent variables include interest in learning, emotional intelligence, and intellectual intelligence. The study employed a descriptive research method. We analyzed the research data using correlational techniques, maintaining a significance level of 95%. The results of the research show that: 1) There is a relationship between interest in learning and PJOK learning achievement with a correlation value (r) of 0.838, which is in the quite strong category with a contribution of 72.2%. 2) There is a relationship between emotional intelligence and PJOK learning achievement with a correlation value (r) of 0.788, which is in the quite strong category with a contribution of 62.1%. 3) For class IX students at Public Middle School 1 Keera, there is a correlation between intellectual intelligence and PJOK learning achievement. The correlation value (r) is 0.800, which is pretty strong and works out to 64.0%. 4) The PJOK learning achievement of class IX students at Public Middle School 1 Keera reveals a significant relationship between interest in learning, emotional intelligence, and intellectual intelligence, with a correlation value (r) of 0.893, indicating a strong contribution of 79.7%.